Obesity in Primary Schools Children in Baquba City - Kahtan, Oday; Ghazal Noaman, Nadhim; Mansour Hemza , Shefaa (Diyala Journal of Medicine, 2020)
Background: Obesity is an abnormal or increased fat accumulation in the body. Body mass index (BMI) defined as a person weight in kilograms divided by the square of his height in meters (kg/m2). It is a very simple index that more commonly used to identify overweight and obesity in adults. For childhood, the amount of body fat differs from that an adult because it differs according to the age and to the sex, so the BMI age- and sex- specific percentiles are used. Obesity in children is a real health problem worldwide especially in developed countries, as well as, it increases in developing countries. Childhood obesity predispose to type 2 diabetics, hypertension, liver and renal disease, cardiovascular diseases and adult obesity. Objective: To detect the prevalence and possible risk factors for childhood obesity in primary schools in Baqubah city from age 6 to 12 years. Patients and Methods: The study was cross-sectional study conducted on a random sample of 6 primary schools from different localities in Baqubah city, followed by a systematic random sample of 308 children aged from 6 to12 years of both sexes. A questionnaire sent to the parents to get information on socio-demographic characteristics, dietary habits, physical activity, family history of obesity and parents education and job. Children's height (cm), weight (Kg), and BMI-for-age were measured. Child's weight status was categorized based on WHO 2007 Growth Reference. This study was included 308 child, the mean age was 9.32±1.9year, 51.9% of the children were males, and 49.1% were female the mean BMI was 18.36±4. Only 2.5% of the studied sample were underweight, while 73.4%, 14.3% and 9.4% were of normal, overweight or obese respectively. Results: About 48% of children in this study eat sweets, 48.5% do regular sports, 48.7% watch TV or mobile for more than 2 hours daily. It was found that 34.7% of children got positive family history of obesity, regarding educational level of parents 39% of mothers and 42.9% of fathers got primary level of education and 33.1% of mothers, 31.2% of fathers got higher than secondary level. Conclusion: The prevalence of overweight and obesity was 23.7% in primary schoolchildren in Baqubah city. The study supports the multi factorial etiology of obesity It showed that sedentary life style, positive family history and eating un healthy foods are risk factors.